Modelling and Forecasting Fiscal Policy and Economic Growth in Nepal - Kharel, Ram Sharan (NRB Economic Review, 2012)
This paper develops a macroeconomic forecasting model focusing on fiscal policy and economic growth in Nepal. The structure of the model, which comprises a total of 14 equations, allows alternative policy options for maintaining fiscal stability and promoting economic growth as well as switching deficit financing between domestic and foreign loans. We use annual data from 1992/93 to 2009/10 to estimate the model and provide out-sample forecasts for 2010/11 to 2012/13, consistent with the current Three Year Plan period, in order to evaluate the plan performance. The empirical evidence suggests that fiscal policy, particularly governments’ capital expenditure affects economic growth positively and also crowds-in private investment. However, there exists a trade-off between fiscal stability and high level of economic growth as the policy goal of achieving both objectives seems to be unattainable. Finally, the out-sample forecast suggests that it is unlikely to attain the targeted economic growth in the Three Year Plan period from the planned fiscal outlay even if it is realized.